2021
DOI: 10.1038/s41598-021-89437-4
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical and antioxidant analysis of medicinal and food plants towards bioactive food and pharmaceutical resources

Abstract: Plants with medicinal properties play an increasingly important role in food and pharmaceutical industries for their functions on disease prevention and treatment. This study characterizes the phenolic composition and antioxidant activity of seven medicinal and food plants, including the leaves of Salvia officinalis L., Rosmarinus officinalis L., Olea europaea L., and Punica granatum L., as well as the leaves and young stems of Ruta graveolens L., Mentha piperita L., and Petroselinum crispum, Mill., by using c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
141
2
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 208 publications
(156 citation statements)
references
References 55 publications
7
141
2
6
Order By: Relevance
“…Among others, plant-based foods reduce the risk of diabetes, cancer, and cardiovascular diseases [ 3 , 4 ] because, in addition to micro- and macronutrients, they contain many bioactive components such as flavanols, carotenoids, and anthocyanins which have been shown to have health-promoting properties. Phenolic compounds are the most abundant secondary metabolites in plants, accumulating in all tissues and organs, and are at the center of research due to their antioxidant, anti-hypertensive, anti-inflammatory, and anti-carcinogenic effects [ 5 , 6 ]. The increasing awareness of society on the subject has rapidly increased the market demand for fresh products rich in nutritional value and functional properties.…”
Section: Introductionmentioning
confidence: 99%
“…Among others, plant-based foods reduce the risk of diabetes, cancer, and cardiovascular diseases [ 3 , 4 ] because, in addition to micro- and macronutrients, they contain many bioactive components such as flavanols, carotenoids, and anthocyanins which have been shown to have health-promoting properties. Phenolic compounds are the most abundant secondary metabolites in plants, accumulating in all tissues and organs, and are at the center of research due to their antioxidant, anti-hypertensive, anti-inflammatory, and anti-carcinogenic effects [ 5 , 6 ]. The increasing awareness of society on the subject has rapidly increased the market demand for fresh products rich in nutritional value and functional properties.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, there are clues that pomegranate leaf infusion (PLI) contains no excitatory and cathartic compositions—found in traditional teas and weight-loss drugs—which suggests high safety without diarrhea, nausea, vomiting, and other adverse reactions [ 12 ]. Our previous work also proved that methanolic extracts of PLs presented remarkably higher total phenolic content and antioxidant capacity than those of several well-known herbs, such as sage, rosemary, and peppermint [ 14 ].…”
Section: Introductionmentioning
confidence: 93%
“…HPLC-MS/MS data reveal that these medicinal plants have high phenolic compounds and could be a promising source of nutraceutical and drug industries [ 22 ]. Colorimetric, chromatographic, and spectrophotometric assays revealed that P. granatum (pomegranate) leaf extract showed a high content of total phenols, ortho-diphenols, tannins, and antioxidant capacity, making pomegranate leaf extract a valued plant source of accepted bioactive molecules for emerging beneficial food–pharma ingredients [ 23 ].…”
Section: Plant Secondary Metabolites As Antioxidant and Antimycobacterial Agentsmentioning
confidence: 99%